1994
DOI: 10.1128/mmbr.58.2.162-210.1994
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the sequence and gene products of the transfer region of the F sex factor.

Abstract: within this region are marked as a double-dashed line. Signal sequence cleavage sites are indicated by vertical arrows below the line. Features of interest, including homology to signature sequences mentioned in the legends to Fig. 3 and 4, are underlined and described below the line. The nick site (A, nt 140 to 141 according to reference 173), the site of the IS3 insertion, and the positions of frameshift mutations (V) are indicated below and above the line, respectively. The restriction sites for common rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
274
0
5

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(284 citation statements)
references
References 193 publications
(422 reference statements)
5
274
0
5
Order By: Relevance
“…These proteins together with the relaxase bind multiple sites within OriT (summarized in ref. [50] and in Fig 2A, lower panel). In the OriT of the F plasmid (F OriT), there are two IHF-binding sites (IHF A and B), two TraY-binding sites (sbyA and sbyC), three TraM-binding sites (sbmA-C), and as mentioned above, two TraIloading sites on each side of nic.…”
Section: Accessory Proteinsmentioning
confidence: 77%
“…These proteins together with the relaxase bind multiple sites within OriT (summarized in ref. [50] and in Fig 2A, lower panel). In the OriT of the F plasmid (F OriT), there are two IHF-binding sites (IHF A and B), two TraY-binding sites (sbyA and sbyC), three TraM-binding sites (sbmA-C), and as mentioned above, two TraIloading sites on each side of nic.…”
Section: Accessory Proteinsmentioning
confidence: 77%
“…in this overview, as it is likely that homologs are functionally equivalent. Based on work on the F factor, the T4SS proteins are organized according to three proposed functions : (1) pilin and pilin processing, (2) pilus tip formation and pilus extension and (3) mating pair stabilization [7] (Figs. 1 and 2; Table 1).…”
Section: F-like T4ss Componentsmentioning
confidence: 99%
“…Kado, unpublished). To circumvent the lack of osa expression in A. tumefaciens, transcription of the osa gene was placed under the control of a constitutive promoter derived from a kanamycin/spectinomycin operon [3,24]. Immunoblot analysis of the subcellular components of A. tumefaciens cells, containing the constitutively expressed osa gene, clearly showed the presence of Osa protein that specifically localizes to the inner membrane fraction.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, by comparative amino acid sequence homology studies, we found that there are relatively close homologies between the amino acid sequence of Osa and that of an IncP plasmid RPI protein involved in fertility inhibition of IncW plasmids such as pSa [3]. Conjugative transfer requires the close association of specific proteins and plasmid DNA to form a complex at the membrane [24,25]. Fertility inhibition may result either through the alteration of such complexes by a protein identified to inhibit plasmid conjugative transfer, or by plugging the postulated pore through which the donor DNA must pass into the recipient cell.…”
Section: Discussionmentioning
confidence: 99%